Legitimate interests of the convicted person - Романов, М. В. (Theory and practice of jurisprudence, 2016)
Problem setting: Institute of the legitimate interests of convicted raises the question of the need to include it in the structure of the legal status of the convicted person. In addition, uncertainty remains the content of legitimate interests of the convicts, and the definition of the legitimate interests of the convicted person. Recent research and publications analysis: Research on the question of the legitimate interests of the convicted devoted attention, including such scholars V.I. Seliverstov, A.V. Lysodyed. But despite the existence of studies of this issue, today it can be argued that there is no consensus regarding the legitimate interests of the convict, no comprehensive and scientifically grounded approach to clarify the question of whether to allocate a structural unit of the legal status of prisoners as a legitimate interest and if you still allocate it, what content to fill this notion. Paper objective: The purpose of this paper is the definition of the legitimate interests of the convicted and their place in the structure of the legal status of the convicted person. Paper main body: The author states that the legal status of the convicted person, as a kind of special status of a person, includes in its structure specific rights and obligations. Given that the status of the convicted based on the general status of the person, which means that the convict including legitimate interests, but their meaning goes beyond the special status of the convicted The paper identified the essential features of legitimate interest: - It is emotional - the intellectual activity of a person which has not yet reached volitional fulfillment; - Has a legitimate interest in the nature of intention, which has the potential possibility of actual implementation; - This intention, when you try to implement it, provides multi-vector activities which usually refers to the different spheres of social relations and different areas of law; - Legitimate interest does not provide security duty for specific action to another entity of certain social relations but can be realized only within certain rights or obligations entity. Conclusions of the research: Despite the fact that the status of the convicted based on the general status of the person, which means that the convict including legitimate interests, but their meaning goes beyond the special status of the convict, involve various areas of law and provides (when you try to implement them) varied and varied activities of both the convict, so other people (like prison service and other enterprises, institutions, organizations and individuals) Аbstract: This paper is devoted to the consideration of the legitimate interests of the convicted person as a pillar of the legal status of the convict. The author determines the real structure of the legal status of the convicted person and establishes whether the legitimate interests of the convict are the necessary elements of the legal status of a convicted person who is serving his sentence. The article gives a definition of the legitimate interests of the convicted and determines their place in the criminal-executive relations. The provisions for the person regarding whom the punishment is implemented are outlined. Key words: legitimate interests of the convicted person, the legal status of the convicted person, the structure of the status of the convicted person, the notion of the legitimate interests of the convicted person, features of legitimate interests of the convicted person.